Autonomic dysfunction in allergic rhinitis assessed by heart rate variability - Irawati, Nina; Poerbonegoro, Niken Lestari; Azzahroh, Faiza; Hanrahan, Joanna Erin (Oto Rhino Laryngologica Indonesiana, 2025)
Background: Allergic rhinitis is a chronic inflammatory condition of the nose mediated by IgE, characterized by symptoms such as nasal congestion, rhinorrhea, repeated sneezing, and nasal itching. Autonomic nervous system dysfunction is a significant factor in the pathophysiology of allergic rhinitis. Purpose: To evaluate autonomic nervous system dysfunction in allergic rhinitis patients using heart rate variability. Case report: A 28-year-old woman with allergic rhinitis who underwent heart rate variability testing, revealed increased parasympathetic nervous system activity. Method: The study involved a literature search through PubMed, EBSCO, Scopus, and ScienceDirect, with screening based on inclusion and exclusion criteria. The selected literatures were critically reviewed using the Oxford Centre for Evidence-based Medicine’s criteria for Etiology Studies. Result: Two cross-sectional studies were identified that matched the case report’s PICO and eligibility criteria. Those studies showed patterns of autonomic nervous system dysfunction, marked by increased parasympathetic and decreased sympathetic activity in allergic rhinitis patients. Conclusion: The findings suggested that autonomic nervous system dysfunction played a role in the pathophysiology of allergic rhinitis, as evidenced by changes in heart rate variability.